2021
DOI: 10.1038/s41598-021-82875-0
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle concentrations of glial fibrillary acidic protein and neurofilament light measured 1 year after traumatic brain injury

Abstract: Traumatic brain injury (TBI) is linked to long-term symptoms in a sub-set of patients who sustain an injury, but this risk is not universal, leading us and others to question the nature of individual variability in recovery trajectories. Extracellular vesicles (EVs) are a promising, novel avenue to identify blood-based biomarkers for TBI. Here, our aim was to determine if glial fibrillary acidic protein (GFAP) and neurofilament light (NfL) measured 1-year postinjury in EVs could distinguish patients from contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…Similarly, significantly increased EV tau and EV P-tau were found in veterans with a history of multiple mild TBIs compared to controls (88). In a recent study of civilians with a history of TBI, EV NfL and EV GFAP measured at 1-year after injury were elevated in patients with moderate to severe TBIs compared to controls, with EV GFAP performing better than EV NfL in distinguishing patients with moderate to severe TBIs from controls (90).…”
Section: Novel Candidate Fluid Biomarkersmentioning
confidence: 89%
“…Similarly, significantly increased EV tau and EV P-tau were found in veterans with a history of multiple mild TBIs compared to controls (88). In a recent study of civilians with a history of TBI, EV NfL and EV GFAP measured at 1-year after injury were elevated in patients with moderate to severe TBIs compared to controls, with EV GFAP performing better than EV NfL in distinguishing patients with moderate to severe TBIs from controls (90).…”
Section: Novel Candidate Fluid Biomarkersmentioning
confidence: 89%
“…No group differences in either NfL or GFAP were observed after one year of injury. Interestingly, a recent study has shown significantly higher levels of EV GFAP in moderate and severe TBIs when compared to controls, but not EV NfL, in a civilian cohort at one year after the injury 33 . It is possible that these discrepancies are due in part to differences in the relative number of severe TBI cases and to a decrease in blood concentrations of EV NfL within the first year after the TBI.…”
Section: Discussionmentioning
confidence: 91%
“…Our group has reported that EV NfL is chronically elevated in SMVs who sustained repetitive mTBIs (3 or more), and associated with severity of neurobehavioral symptoms 15 . Elevated EV levels of GFAP, but not NfL, have been observed in a civilian population with history of moderate or severe TBI one year post-injury 33 . Importantly, mTBIs are heterogenous according to clinical presentation and neuroimaging findings 34 , 35 .…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Acute expressions of EV markers were particularly sensitive to diffuse injury compared to focal injuries (GFAP, NfL), with excellent prognostic utility for early mortality (UCH-L1, 100 % sensitivity and specificity) (Mondello et al, 2020a). When within-EV levels of GFAP and NfL were examined at 1-year post-injury, patients with moderate and severe TBI exhibited higher concentrations of GFAP relative to healthy controls (AUC = 0.858 and 0.876, respectively), while within-EV GFAP levels were not significantly different between patients with mild TBI and controls (Flynn et al, 2021). Additionally, higher levels of EV GFAP and EV NfL were significantly associated with lower Glasgow Outcome Scale -Extended scores (i.e., worse outcomes), suggesting that EV cargo can still provide valuable prognostic utility at chronic post-injury time points; however, the exact mechanisms by which these markers are chronically elevated in the CNS, packaged in EVs, and then translocated to the bloodstream remain unknown.…”
Section: Clinical Utility Of Evs As Biomarkers For Tbi-comparison Of Evmentioning
confidence: 99%